Dust explosions and collapsed ductwork. (March 2021) - Cox, Brenton L.; Hietala, David C.; Ogle, Russell A.
Abstract: One of the more obvious consequences of a dust deflagration inside process equipment or a structure is the mechanical damage caused by shock (compression) waves. This overpressure damage is revealed through the displacement of equipment, the outward deformation or rupture of enclosures constructed of ductile materials, or the projection of missiles. However, a different type of damage is sometimes observed in the ductwork connecting process equipment. In particular, the ductwork is collapsed as if it were subjected to an external, rather than an internal pressure. The phenomenon that causes this collapse of thin-walled conduit is a gas dynamic process called an expansion wave. When a dust deflagration travels through a conduit, it accelerates and causes a rise in pressure. When the dust deflagration is vented (say through a deflagration vent), the discharge of the high-pressure combustion products causes the formation of an expansion wave that travels in the reverse direction of the original discharge. The expansion wave causes the pressure in the ductwork to fall below atmospheric pressure. The sub-atmospheric pressure, in turn, causes the ductwork to fail by buckling. In this study, we examine the gas dynamics of the expansion wave, demonstrate how to calculate the degree of pressure drop caused by the expansion wave, and illustrate the concept with case studies of dust explosions. Highlights: Not all damage from explosion is necessarily from overpressure. Compression wave (ΔP > 0) is often followed by an expansion wave (ΔP < 0). Collapse pressure may be much lower in magnitude than rupture pressure. Calculating collapse pressure is non-trivial and scenario dependent.